A fuzzy two-stage DEA approach for performance measurement: real case of agility performance in dairy supply chains. (1st January 2012) - Khalili-Damghani, Kaveh; Taghavi-Fard, Mohammad; Abtahi, Amir-Reza
In this paper, a fuzzy two-stage data envelopment analysis (FTSDEA) has been proposed. Each decision making unit (DMU) has been supposed to make up of two serially connected sub-DMUs. The vagueness of measures has been represented using linguistic terms parameterised through fuzzy sets. Mathematical modelling of proposed FTSDEA results in great reduction of computational efforts. The proposed FTSDEA associates an interval efficiency score to each DMU and sub-DMU. A Monte-Carlo simulation procedure has been supplied to rank and discriminate the interval efficiency scores of efficient DMUs and sub-DMU. A conceptual model including providers of agility, capabilities of agility, and goals of supply chain has been proposed. The model has been associated to a two-stage DMU with fuzzy inputs and outputs. Providers of agility are changed into capabilities of agility in first stage. Then, capabilities of agility are changed into goals of supply chain in second stage. The proposed approach has been applied in real case study of dairy supply chains.